Analysis of Air Quality during the COVID-19 Pandemic Lockdown in Naples (Italy) - Alessia Sannino; Mariagrazia D’Emilio; Pasquale Castellano; Salvatore Amoruso; Antonella Boselli (Aerosol and Air Quality Research)
Abstract Lockdown measures applied in the aftermath of the COVID-19 pandemic spread to Italy in the period March 13th–May 4th strongly limited the social and industrial activities with consequent effects on the air pollution. Here we report a study on the influence of the lockdown measures on the air quality in the city of Naples (Italy). The comparison of the levels of various gaseous pollutants (C6H6, CO, NO2 and SO2) and particulate matter (PM10, PM2.5, PM1) at ground level as well as of atmospheric aerosol properties registered by remote sensing techniques during the lockdown period with the values observed in the earlier months and during the same period of the previous year is used to gain interesting information on the environmental impact of the human activities. Our findings show a rather significant reduction of the pollution due to NO2 (49–62%) in urban as well as in green suburban area, while CO and SO2 showed a more important reduction in urban or industrial districts of the city (50–58% and 70%, respectively). Particulate matter at ground level is also affected but to a more limited extent (29–49%). Nevertheless, characterization of atmospheric aerosol columnar properties suggests an interesting variation of its composition. The observed features have been associated to the strong meteorological interference from Saharan Dust in the Mediterranean area also affecting the city of Naples.